Boundedness of weak solutions of a nondiagonal singular parabolic system of three equations - Portnyagin, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
The $L^{∞}$-estimates of weak solutions are established for a quasilinear nondiagonal parabolic system of singular equations whose matrix of coefficients satisfies special structural conditions. A procedure based on the estimation of linear combinations of the unknowns is used.